HUBUNGAN DAYA LEDAK OTOT TUNGKAI DENGAN KETEPATAN TEMBAKAN KE GAWANG TIM SEPAKBOLA SMA OLAHRAGA MASMUR PEKANBARU - Agust, Kristi; ', Rifnaldi; ', Saripin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : Based on the researcher’s observation of SMA Sport Masmur Pekanbaru city. Researcher found many student have frequent errors in shooting, when the student shooting ball not on target so in the game often lose, shooting technique a weakness of student in SMA Sport Masmur Pekanbaru City. The purpose of this research is to see the corrrelation of explosive power leg muscle with accuracy to shooting of SMA Sport Masmur Pekanbru. Population in this research were all students of SMA Sport Masmur Pekanbru who were 18 people. Based on population that is not so large and within the limits the researchers set the whole population is used as a sample. The research sample as many as 18 people. Research instrument used explosive power leg muscles test and the result of shooting ball. Data were analyzed by product moment correlation. Based on research results, it can be concluded as follows : Shows that there is contribution explosive power leg muscles with accuracy shooting, which shows rhitung (0,538)> rtabel (0,482) padaα=0,05Key word : Explosive Power Leg Muscle, Shooting.